Gambaran Posisi Duduk dan Derajat Fungsional Pasien Low Back Pain di Poliklinik Saraf Rumah Sakit Umum Daerah Waled - Salman Mursyidan Baldan; Moch Irwansyah Dharmansyahi; Kati Sriwiyati (KOLONI, 2026)
Low back pain (LBP) is a common musculoskeletal disorder that may cause limitations in functional activities. One of the risk factors associated with LBP is prolonged non-ergonomic sitting posture. This study aimed to describe sitting position and functional degree among patients with low back pain at the Neurology Polyclinic of Waled Regional General Hospital. This study used a descriptive observational design with a cross-sectional approach. The population consisted of all low back pain patients visiting the Neurology Polyclinic of RSUD Waled from May to July 2024. A total of 57 respondents were selected using the total sampling method. The variables studied were sitting position and functional degree of low back pain. Data were collected using a sitting position questionnaire and the Back Pain Functional Scale (BPFS) instrument. Data analysis was performed using univariate analysis with frequency distribution, percentage, mean, and standard deviation. Most respondents were male, accounting for 32 patients (56.1%), with the highest age group being late adulthood 37–45 years consisting of 20 patients (35.8%). The most common sitting position was slightly bent posture in 17 respondents (29.8%), followed by leaning and upright sitting positions in 15 respondents each (26.3%), and hunched posture in 10 respondents (17.5%). The mean BPFS score was 42 ± 13.91, indicating that most patients had a good functional ability category. Slightly bent sitting posture was the most common sitting position found among low back pain patients at the Neurology Polyclinic of RSUD Waled. The functional degree based on BPFS demonstrated that the majority of patients still had relatively good functional ability.